Canva-Based Interactive Flashcard Development Needs Analysis to Optimise Early Reading Learning in Elementary Schools - Utami, Dyah Setyo; Jaenudin, Riswan; Hudaidah, Hudaidah (Papanda Publisher, 2025)
Early reading skills are an important foundation for the success of student learning at the next level. However, many elementary school grade I students still have difficulty recognising letters, spelling, and understanding simple words due to monotonous learning dominated by the use of textbooks. This condition shows the need for learning media innovations that are more interactive, interesting, and in accordance with the learning characteristics of early childhood students. This study aims to analyse the need for the development of Canva-based interactive flashcards to optimise early reading learning in grade I elementary school. The method used is Research and Development (R&D) with a qualitative descriptive approach. Data were collected through semi-structured interviews with one grade I teacher and closed interviews with 30 grade I students at SDN 4 Ngulak, Sanga Desa District, Musi Banyuasin Regency. Data analysis was carried out in a qualitative descriptive manner with the Miles and Huberman model through three stages, namely data reduction, data presentation, and conclusion drawn. The results of the study showed that the analysis of students' needs for the development of Canva-based flashcard interactive media was in the very high category, with the acquisition of pedagogical aspects of 98.89%, technical aspects of 94.17%, cognitive aspects of 78.33%, aesthetic aspects of 96.67%, and evaluation aspects of 91.67%. The teacher also emphasised the importance of digital media that is visual, practical, and supports multisensory learning through a combination of text, images, and sound. These findings indicate that the development of Canva-based interactive flashcards has the potential to be a practical learning media innovation to improve the motivation and early reading ability of elementary school students.